Psychometric Properties of the Short Forms of the Social Interaction Anxiety Scale and the Social Phobia Scale in a Chinese College Sample - Ouyang, Xueyuan (Front Psychol, 2020)
This study was carried out to examine the factor structure and psychometric properties of the Social Interaction Anxiety Scale (SIAS) and Social Phobia Scale (SPS) in a sample of 1,001 Chinese college students (male: 34%; female: 66%). Confirmatory factor analysis (CFA) indicated that the two-factor shortened version of the SIAS-6/SPS-6 fit the data well. In addition, the item response theory (IRT) method confirmed the construct and items for the 12 items of the SIAS-6/SPS-6 with satisfactory discrimination, threshold parameters, and test information curve. It was concluded that the factor structure and psychometric properties of the SIAS-6/SPS-6 support their use for such assessment in a Chinese college sample.